2015
DOI: 10.1080/15384047.2015.1019185
|View full text |Cite
|
Sign up to set email alerts
|

Imp2 regulates GBM progression by activating IGF2/PI3K/Akt pathway

Abstract: Glioblastomas multiforme (GBM) are the most frequently occurring malignant brain cancers. Treatment for GBM consists of surgical resection and subsequent adjuvant radiation therapy and chemotherapy. Despite this, GBM patient survival is limited to 12-15 months, and researchers are continually trying to develop improved therapy options. Insulin-like growth factor 2 mRNA-binding protein 2 (Imp2) is known to be upregulated in many cancers and is known to regulate the signaling activity of insulin-like growth fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
74
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(75 citation statements)
references
References 43 publications
1
74
0
Order By: Relevance
“…[11,31a,b,c,d] but only a limited number of RNAbinding maternal proteins in mice that are involved in the oocyte-to-embryo transition have been reported previously. [16,19,21] However, the contribution of maternal Imp2 mRNA and protein during mouse embryogenesis has remained to be studied. [16,19,21] However, the contribution of maternal Imp2 mRNA and protein during mouse embryogenesis has remained to be studied.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[11,31a,b,c,d] but only a limited number of RNAbinding maternal proteins in mice that are involved in the oocyte-to-embryo transition have been reported previously. [16,19,21] However, the contribution of maternal Imp2 mRNA and protein during mouse embryogenesis has remained to be studied. [16,19,21] However, the contribution of maternal Imp2 mRNA and protein during mouse embryogenesis has remained to be studied.…”
Section: Discussionmentioning
confidence: 99%
“…[19,41] It has been reported that Imp2 promotes IGF2 mRNA translation. [19] Overexpression of Imp2 increases the level of IGF2 protein in cell lines, and silencing of Imp2 decreases these levels. [19] Overexpression of Imp2 increases the level of IGF2 protein in cell lines, and silencing of Imp2 decreases these levels.…”
Section: Discussionmentioning
confidence: 99%
“…Immunohistochemical studies were performed as previously reported [15]. Normal brain tissue was obtained from a frontal lobe trauma patients.…”
Section: Methodsmentioning
confidence: 99%
“…IGF2BP2 has been recently reported to be overexpressed in several types of solid cancers [9,10]. IGF2BP2 overexpression promotes glioblastoma multiforme (GBM) progression by activating the IGF2/PI3K/Akt pathway and makes GBM resistant to temozolomide treatment [11]. In addition, IGF2BP2 promotes hepatocarcinogenesis by inducing inflammation [12].…”
Section: Introductionmentioning
confidence: 99%